2014
DOI: 10.1002/ps.3931
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution and sequential sampling plans for Tuta absoluta (Lepidoptera: Gelechiidae) in greenhouse tomato crops

Abstract: The enumerative sampling plan required 87 or 343 leaves to estimate the population density in extensive or intensive ecological studies respectively. Binomial plans would be more practical and efficient for control purposes, needing average sample sizes of 17, 20 and 14 leaves to take a pest management decision in order to avoid fruit damage higher than 1% in cultivars with big, medium and small fruits respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 37 publications
2
26
0
2
Order By: Relevance
“…Under laboratory conditions indicated that “Cal JN3” was the most susceptible to infestation and “Primo Early” and “Early Urbana Y” were the most resistant cultivars to T. absoluta (Ghaderi et al, ). The present findings are in line with those of earlier studies that found the damage caused by T. absoluta on various crops to be correlated with the density of mines and larvae (Cely, Cantor, & Rodríguez, ; Cocco et al, ; Tropea Garzia et al, ). Hence, the yield loss and the direct fruit damage in tomato was a result of the percentage of leaf infestation by T. absoluta .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Under laboratory conditions indicated that “Cal JN3” was the most susceptible to infestation and “Primo Early” and “Early Urbana Y” were the most resistant cultivars to T. absoluta (Ghaderi et al, ). The present findings are in line with those of earlier studies that found the damage caused by T. absoluta on various crops to be correlated with the density of mines and larvae (Cely, Cantor, & Rodríguez, ; Cocco et al, ; Tropea Garzia et al, ). Hence, the yield loss and the direct fruit damage in tomato was a result of the percentage of leaf infestation by T. absoluta .…”
Section: Discussionsupporting
confidence: 93%
“…Tomato, Solanum lycopersicum L., is an economically important crop worldwide, ranking fourth among vegetables worldwide (Bawin et al, ; Retta & Berhe, ). One of the most destructive pests of tomato is the tomato leaf miner, Tuta absoluta (Meyrick) (Lepidoptera: Gelechiidae), whose larval feeding causes 50%–100% yield losses in many areas (Cocco, Serra, Lentini, Deliperi, & Delrio, ; Tropea Garzia, Siscaro, Biondi, & Zappalà, ). This pest is native to South America, and it has spread to Afro‐Eurasian and Middle Eastern countries, including Albania, Algeria, France, Italy, Netherlands, Germany, Denmark, Greece, Cyprus, Egypt, Tunisia, Kuwait and also Iran (Baniameri & Cheraghian, ; Desneux et al, ; Urbaneja, Vercher, Navarro, Garcıa Marı, & Porcuna, ).…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the efficiency of chemical control of tomato leaf miner infestations has been poor because of (1) the entophytic habit of its larvae, which are protected in the leaf mesophyll or inside fruits [8,36] and (2) pest resistance against a number of applied insecticides [6,7,19]. In order to reduce the excessive use of insecticides in tomato fields, environmentally sound control strategies have been developed, including cultural control measures (e.g.…”
Section: Chemical Control Methodsmentioning
confidence: 99%
“…Numerous sequential sampling plans developed for arthropods in field crops have used 10% as an acceptable level of error (i.e., a and b parameters; Cusson et al 1990, Naranjo and Hutchison 1997, Cocco et al 2015. In the present study, the upper and lower stop lines for 5% and 10% error (i.e.…”
Section: Discussionmentioning
confidence: 81%